Rancang Bangun Sistem Informasi Monitoring Marketing Penerimaan Mahasiswa Baru: (Studi Kasus LP3I Tasikmalaya) - Haisyam Maulana (Jurnal Sistem Informasi Galuh, 2023)
Industry 4.0 requires various parties to follow the changes. Effective and efficient makes the main focus on industry 4.0, although LP3I Tasikmalaya already has a system, but it still does not meet the demands of user needs and industry 4.0 competition. Telleselling, MCV, and WA-Blast, are the activities of the presenters of LP3I Tasikmalaya which should have been facilitated by the system but in the field they use Googgle Sheets because the system is considered not to meet the needs and makes it difficult. The aim of the research is to designing and building an information system for Monitoring Marketing in LP3I Tasikmalaya, so that it can address potential data storage problems, update potential data, thereby providing fast and accurate information in the Marketing Division. The collection method uses observation and interviews while the development of the system used is the waterfall model, which consists of stages: analysis, design, coding, and testing, as well as tools in designing the system are DFD (Data Flow diagram). The implementation uses software, namely Android Studio and MySQL Servers. The result of this research is a Digital Marketing Information System that can simplify the process of information on the Marketing Division of LP3i Tasikmalaya in real time.